2019
DOI: 10.1177/0731948719851514
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of Implementation in the Field of Learning Disabilities

Abstract: Decades of research and billions of dollars have been spent to develop and evaluate evidence-based interventions and develop multitiered systems of support (MTSS) toward the goal of more effectively delivering interventions and improving student outcomes. Available evidence, however, suggests interventions are often adopted slowly and delivered with poor fidelity, resulting in uninspiring outcomes for students. The field of implementation science has emerged to address the science-to-practice gap in human serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…For example, our results showed that when students with LD and/or MD receive instruction from researchers or researchers collaborating with school personnel, we can expect an increase of between 76 to 77 percentile points compared with a gain of 60 to 61 percentile points when school personnel deliver the intervention. Evidence suggests that interventions “are often adopted slowly and delivered with poor fidelity, resulting in uninspiring outcomes for students” (Sanetti & Luh, 2019, p. 1). Implementing an evidence-based practice requires buy-in from practitioners in terms of its acceptability and feasibility.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our results showed that when students with LD and/or MD receive instruction from researchers or researchers collaborating with school personnel, we can expect an increase of between 76 to 77 percentile points compared with a gain of 60 to 61 percentile points when school personnel deliver the intervention. Evidence suggests that interventions “are often adopted slowly and delivered with poor fidelity, resulting in uninspiring outcomes for students” (Sanetti & Luh, 2019, p. 1). Implementing an evidence-based practice requires buy-in from practitioners in terms of its acceptability and feasibility.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should address the limitations of these studies, particularly with attention to treatment fidelity. In line with other areas of special education (e.g., Sanetti & Luh, 2019;Swanson et al, 2013), many studies in this review lacked measures of treatment fidelity or offered only thin depictions. As employment interventions tend to be highly individualized and conducted by many stakeholders across multiple settings (see , assessing fidelity can be particularly challenging but takes on heightened importance for understanding how stakeholders can improve employment gaps that have persisted for decades (Trainor et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A further challenge concerns the complexity of some RTI models, and the related failure of supervisors to assess intervention fidelity. This can result in problems of participant selection and programme implementation (Sanetti & Luh, 2019). There is some evidence from a US national evaluation (Balu et al, 2015) that the upper end of students for whom RTI had been deemed appropriate (scoring at or just below the 40th centile) failed to beneft from intervention.…”
Section: How Can We Best Help All Struggling Readers?mentioning
confidence: 99%